Effect of prehabilitation exercises on postoperative frailty in patients undergoing laparoscopic colorectal cancer surgery - Yang, Fuyu; Yuan, Ye; Liu, Wenwen; Tang, Chenglin; He, Fan; Chen, Defei; Xiong, Junjie; Huang, Guoquan; Qian, Kun (Frontiers in Oncology, 2024)
BackgroundTo improve perioperative frailty status in patients undergoing laparoscopic colorectal cancer surgery (LCCS), we explored a new intensive prehabilitation program that combines prehabilitation exercises with standard enhanced recovery after surgery (ERAS) and explored its impact.MethodsWe conducted a prospective randomized controlled trial. Between April 2021 to August 2021, patients undergoing elective LCCS were randomized into the standardized ERAS (S-ERAS) group or ERAS based on prehabilitation (group PR-ERAS). Patients in the PR-ERAS group undergoing prehabilitation exercises in the perioperative period in addition to standard enhanced recovery after surgery. We explored the effects of this prehabilitation protocol on frailty, short-term quality of recovery (QoR), psychological status, postoperative functional capacity, postoperative outcomes, and pain.ResultsIn total, 125 patients were evaluated, and 95 eligible patients were enrolled and randomly allocated to the S-ERAS (n = 45) and PR-ERAS (n = 50) groups. The Fried score was higher in the PR-ERAS group on postoperative day (7 (2(2,3) vs. 3(2,4), P = 0.012). The QoR-9 was higher in the PR-ERAS group than in the S-ERAS group on the 1st, 2nd, 3rd, and 7th postoperative days. The PR-ERAS group had an earlier time to first ambulation (P < 0.050) and time to first flatus (P < 0.050).ConclusionPrehabilitation exercises can improve postoperative frailty and accelerate recovery in patients undergoing LCCS but may not improve surgical safety. Therefore, better and more targeted prehabilitation recovery protocols should be explored.Clinical trial registrationwww.clinicaltrials.org, identifier NCT04964856.